IMPROVEMENT OF LUMINESCENT PROPERTIES OF PBWO4 BY DOPING WITH GD3+ IONS - Zhou D.; Chen Y.; Shi C.; Liu B. (My University, 2002)
The luminescent properties of PbWO4: Gd3+ was studied. The luminescence of Gd3+ in PbWO4:Gd3+ was quenched. It is possible that the excitation states of Gd3+ locate in the conduction band of PbWO4 crystal. The luminescent intensity of the green and the blue band of PbWO4 emission increases by doping about 0.005% and 0.01% (molar fraction) Gd3+ respectively. Mechanism of this enhancement of PbWO4:Gd3+ luminescence is probably due to energy transfer from Gd3+ to PbWO4 host in the crystal. The PbWO4 doped with low concentration of Gd (about 0.005%-0.01%)is a good scintillating material.